COMPARATIVE STUDY ON MOUTH DISSOLVING FILM AND MOUTH DISSOLVING TABLET FOR ETORICOXIB DRUG - Durgesh Sharma; Mr. D K Vishwakarma; Dr. Jai Narayan Mishra (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The objective of present study is investigated formulation development and evaluated of etoricoxib mouth dissolving tablet by using direct compression method and mouth dissolving film by solvent casting method, in different concentrations to enhance the disintegration profile. Etoricoxib is an anti-rheumatoid arthritis drug, which is commonly prescribed for treatment of rheumatoid arthritis, osteoarthritis and gout. It is a slightly soluble in water and it is cox-2 inhibitor. Etoricoxib has long biological halflife (22hrs). In the present study, MDTs and MDFs of etoricoxib were prepared by for better patient compliance and immediate action in rheumatoid arthritis, and osteoarthritis. The tablets were prepared by using superdisintegrants such as croscarmellose, sodium starch glycolate, In the MDFs film forming polymer meltodextrin, PVA, HPMC are used and increase the disintegration profile.